Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

17. If [tex]$y=\frac{(1-x)^{20}}{(1+x)^{25}}$[/tex], find [tex]$\frac{d y}{d x}$[/tex].

A. [tex]y\left(\frac{20}{1+x}+\frac{25}{1-x}\right)[/tex]

B. [tex]y\left(\frac{25}{1+x}+\frac{20}{1-x}\right)[/tex]

C. [tex]-y\left(\frac{25}{1-x}+\frac{20}{1+x}\right)[/tex]

D. [tex]-y\left(\frac{20}{1-x}+\frac{25}{1+x}\right)[/tex]


Sagot :

To solve the problem of finding the derivative [tex]\(\frac{dy}{dx}\)[/tex] for the given function [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex], let's follow the steps to find the derivative.

1. Identify the function [tex]\( y \)[/tex]:
[tex]\[ y = \frac{(1-x)^{20}}{(1+x)^{25}} \][/tex]

2. Apply the quotient rule:
The quotient rule for derivatives states that if you have a function [tex]\( y = \frac{u}{v} \)[/tex], then its derivative is given by:
[tex]\[ \frac{dy}{dx} = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} \][/tex]

Here, [tex]\( u = (1-x)^{20} \)[/tex] and [tex]\( v = (1+x)^{25} \)[/tex].

3. Differentiate [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ \frac{du}{dx} = 20(1-x)^{19} (-1) = -20(1-x)^{19} \][/tex]
[tex]\[ \frac{dv}{dx} = 25(1+x)^{24} (1) = 25(1+x)^{24} \][/tex]

4. Apply the quotient rule formula:
[tex]\[ \frac{dy}{dx} = \frac{(1+x)^{25} \cdot [-20(1-x)^{19}] - (1-x)^{20} \cdot [25(1+x)^{24}]}{(1+x)^{50}} \][/tex]

5. Simplify the numerator:
[tex]\[ \frac{dy}{dx} = \frac{-20(1-x)^{19}(1+x)^{25} - 25(1-x)^{20}(1+x)^{24}}{(1+x)^{50}} \][/tex]

Factor out the common terms:
[tex]\[ \frac{dy}{dx} = \frac{(1-x)^{19}(1+x)^{24}[-20(1+x) - 25(1-x)]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24}[-20 - 20x - 25 + 25x]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24}[-45 + 5x]}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{(1-x)^{19}(1+x)^{24} \cdot 5(-9 + x)}{(1+x)^{50}} \][/tex]
[tex]\[ = \frac{5(1-x)^{19}(x - 9)}{(1+x)^{26}} \][/tex]

6. Express the answer in terms of [tex]\( y \)[/tex]:
[tex]\[ \frac{dy}{dx} = 5 (x-9) \frac{(1-x)^{19}}{(1+x)^{26}} \][/tex]

Since [tex]\[ \frac{(1-x)^{20}}{(1+x)^{25}} = y \][/tex]
[tex]\[ = \frac{dy}{dx} = 5 \cdot \frac{x-9}{(1+x)} y \][/tex]

Given the derived solution matches in form, we look at the positive and negative signs in the options to finalize:

[tex]\[ \frac{dy}{dx} = -y \left(\frac{25}{1-x} + \frac{20}{1+x}\right) \][/tex]

Thus the correct answer is:
[tex]\[ \boxed{-y\left(\frac{25}{1-x}+\frac{20}{1+x}\right)} \][/tex]